2013
DOI: 10.1002/jsc.1945
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Change and Decision Making in an Emerging Nation: An Exploratory Assessment of Iranian Manufacturing Firms

Abstract: Businesses that combined cost leadership and differentiation strategies reported the greatest satisfaction with overall performance, but political and economic instability associated with trade sanctions continue to be a key concern for executives in Iran.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 81 publications
0
27
0
7
Order By: Relevance
“…Context Process Studies of strategic decisions in emerging markets have identified significant, and institutionally related, differences in their type compared to those undertaken in developed economies (Taslak, 2004;Elbanna and Child, 2007a;Zamani et al, 2013). The overarching aim of this research is to investigate the extent to which strategic decision implementation in Jordan is also influenced by these political and economic institutional differences.…”
Section: Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…Context Process Studies of strategic decisions in emerging markets have identified significant, and institutionally related, differences in their type compared to those undertaken in developed economies (Taslak, 2004;Elbanna and Child, 2007a;Zamani et al, 2013). The overarching aim of this research is to investigate the extent to which strategic decision implementation in Jordan is also influenced by these political and economic institutional differences.…”
Section: Contentmentioning
confidence: 99%
“…It has also drawn attention to the context-specific nature of strategic management (Xu and Meyer, 2013). Strategic decision making in an emerging market context (Iran) has been studied (Zamani et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Business strategy typologies are a kind of frameworks which identify multiple business strategies available to a business (Anwar et al, 2016). Typologies provide a theoretical basis to identify different strategic groups across industries (Parnell, 2011;Zamani et al, 2013). The typologies developed by Miles and Snow (1978) and Porter (1980) received much scholarly attention and remained among the most widely cited and tested models.…”
Section: Business Strategy Typologiesmentioning
confidence: 99%
“…product leadership, and customer intimacy. According to Parnell (2011) and Zamani et al (2013), business strategy typologies are frameworks that identify multiple competitive strategies available to business units. Typologies are developed and used as a theoretical basis for identifying strategic groups across industries.…”
Section: Introductionmentioning
confidence: 99%